«Migratory» phenotype of lymphocytes in peripheral blood in patients with uveal melanoma in varying efficiency preserving therapy (Ukrainian Journal of Ophthalmology, 2026)
Provided by a whole complex of signals — one of them is the most significant signal coming from IL-2 as well as chemokines such as RANTES that are not only chemoattractant but also inactivator of T — cells. All these effects lead to activation of lymphocytes, which compared to resting one can cross the blood-barrier.The aim of this study was to investigate the relationship between «immigration» and lymphocyte phenotype marker of apoptosis and progression of uveal melanoma in organ-preserving treatment. Material and methods. A histoimmunocytochemical method by using monoclonal antibodies compared the level of expression CD54+ and CD95+ lymphocytes in the peripheral blood of patients with uveal melanoma with different efficacy of organ preserving treatment. Depending on the outcome of treatment (photocoagulation + ?-Application therapy) there were formed two groups: 116 patients with tumor regression, and 34 patients with progressive growth and subsequent enucleation of the eye. The statistical processing has been done with the help of the program (Statistica 7.0 ).Results. Significant differences were observed in patients with uveal melanoma with different efficacy of organ preserving treatment in absolute and relative values of CD54 + and CD95+. In tumor regression the absolute value of the expression level of the marker CD54+ in the peripheral blood lymphocytes was (278.3 (183.9)) cells / mcl and relative value — (19.2 (9.2)) % relative to the absolute (190.0 (129.5)) cells / mcl and relative (14.9 (7.1)) % value in patients with progressive tumor growth (p1 = 0.03 and p2= 0.04, respectively). The absolute value of the expression level of the marker of apoptosis CD95+ in patients with uveal melanoma with tumor regression was (325.2 (206.3)) cells / mcl, and the relative value of — (21.8 (9.6)) % relative to the absolute (218 6 (133.8))cell/mcl, and a relative value (16.2 (6.3)) % in tumor progression (P1 = 0.02 and P2 = 0.01, respectively). To preserve the eye during the treatment is extremely important to regulate highly activated T -cells and suppression of the immune response to the blocking of inflammation by means of an excess of apoptosis (CD95 +).Conclusion. The level of expression of the molecular markers of activation CD54+ and CD95+ in patients with regression of uveal melanoma was significantly higher than in the patients with progressive tumor growth and subsequent enucleation after organ preserving treatment.
Keywords: uveal melanoma; molecular markers of activated lymphocytes; predict treatment outcome